A cross‐cultural examination of subordinates' perceptions of and reactions to abusive supervision. (25th November 2014) - Vogel, Ryan M.; Mitchell, Marie S.; Tepper, Bennett J.; Restubog, Simon L. D.; Hu, Changya; Hua, Wei; Huang, Jui‐Chieh; Zhu, Weichun; He, Hongwei; Law, Kenneth S.; Farh, Jiing‐Lih
Summary This manuscript explores cross‐cultural differences in reactions to perceived abusive supervision. Based on an integration of fairness heuristic theory with principles about cross‐cultural differences in the importance of hierarchical status, we theorize that subordinates from the Anglo culture perceive and react to abusive supervision more negatively than subordinates from the Confucian Asian culture. The predictions were tested within two field studies. Study 1 results show that culture moderated the direct effect of perceived abusive supervision on interpersonal justice and the indirect effects of perceived abusive supervision (via interpersonal justice) on subordinates' trust in the supervisor and work effort. The negative effects of perceived abusive supervision were stronger for subordinates within the Anglo versus the Confucian Asian culture; subordinates from Anglo culture compared with Confucian Asian culture perceived abusive supervision as less fair. Perceived abusive supervision indirectly and negatively influenced subordinates' trust in the supervisor and work effort. Study 2 replicated the findings from Study 1 and extended them to show culture (Anglo vs. Confucian culture) moderated the effects because it influences subordinates' power distance orientation. Copyright © 2014 John Wiley & Sons, Ltd.